1991
DOI: 10.1016/0736-5748(91)90023-f
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c‐myc and c‐fos oncogenes in different rat brain regions during postnatal development

Abstract: We have studied the expression of c-myc and c-fos proto-oncogenes in various areas of the central nervous system during postnatal development. c-myc mRNA levels increased during the first 5 days and then decreased over the next 15 days in all nervous regions studied. c-fos mRNA levels changed in a different way in four brain areas. While in cerebral cortex and cerebellum there was a sharp decrease during the first 10 days, in white matter and hypothalamus c-fos transcript levels remained high during the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
1
5
0
2
Order By: Relevance
“…c-myc expression has been shown to increase in normal lymphocytes stimulated to divide by mitogen and growth factors and to decrease when the cells are stopped in GdG, (Lomo et al 1987), suggesting a correlation with proliferative activity. These results were confirmed in many normal (Parma et al 1991) and tumour cells (Harding et af. 1992).…”
Section: Discussionsupporting
confidence: 53%
“…c-myc expression has been shown to increase in normal lymphocytes stimulated to divide by mitogen and growth factors and to decrease when the cells are stopped in GdG, (Lomo et al 1987), suggesting a correlation with proliferative activity. These results were confirmed in many normal (Parma et al 1991) and tumour cells (Harding et af. 1992).…”
Section: Discussionsupporting
confidence: 53%
“…Even though the clonal expansion of increasing malignant tumor cells in nascent medulloblastomas results from the accumulation of genetic lesions, the failure of residual neuroectodermal cells to differentiate or to undergo apoptosis in the post‐natal brain could provide the cellular substrate for these genetic lesions. Given the central role that c‐ myc is thought to play in regulating cell proliferation, cell differentiation and cell death in the developing cerebellum (Hirvonen et al, 1990; Parma et al, 1991; Ruppert et al, 1986), one may hypothesize that c‐ myc plays a contributory role in the molecular pathogenesis of medulloblastoma. Indeed, c‐ myc gene amplification is a common finding in cell lines derived from medulloblastomas (Batra et al, 1994; Bruggers et al, 1998; Pietsch et al, 1994; Selvanayagam et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the expression of IEGs during the early postnatal period undergoes a significant change and does so in a region‐specific manner. In the cerebral cortex and cerebellum of neonatal rats, constitutive levels of c‐ fos mRNA undergo a sharp decline during the first 10 days of postnatal development (Parma et al, 1991). However, in the hypothalamus, levels of c‐ fos mRNA remain high during this period and decrease only at a later age.…”
Section: Discussionmentioning
confidence: 99%